A SIMPLE METHOD FOR DETERMINING LOCATION OF FORAGING ANT NESTS USING LEAF-CUTTING ANTS AS A MODEL - Fowler, H. G.; Schlindwein, M. N.; Schlittler, F. M.; Forti, Luiz Carlos [UNESP] (Blackwell Wissenschafts Verlag Gmbh, 1993)
In many situations, it is difficult to evaluate the location of nests of ants, especially in tropical systems, or to determine which trail system corresponds with which nest, as in the case of high-density populations of leaf-cutting ants, Atta spp. Fragments of colored drinking straws coated with an attractant, generally vegetable oil and/or a starchy carbohydrate, are carried by ants and following removal of the attractant are deposited in middens, allowing determination of the origin of foraging workers.